Lamivudine 24-month-long prophylaxis is a safe and efficient choice for the prevention of hepatitis B virus reactivation in HBsAg-negative/HBcAb-positive patients with advanced DLBCL undergoing upfront R-CHOP-21 - Giordano, Claudia; Picardi, Marco; Pugliese, Novella; Vincenzi, Annamaria; Abagnale, Davide Pio; De Fazio, Laura; Giannattasio, Maria Luisa; Fatigati, Carmina; Ciriello, Mauro; Salemme, Alessia; Muccioli Casadei, Giada; Vigliar, Elena; et al. (Frontiers in Oncology, 2023)
Introduction Occult hepatitis B infection (OBI) is a condition where replication-competent hepatitis B virus-DNA (HBV-DNA) is present in the liver, with or without HBV-DNA in the blood [<200 international units (IU)/ml or absent] in HB surface antigen (HBsAg)-negative/HB core antibody (HBcAb)-positive individuals. In patients with advanced stage diffuse large B-cell lymphoma (DLBCL) undergoing 6 cycles of R-CHOP-21+2 additional R, OBI reactivation is a frequent and severe complication. There is no consensus among recent guidelines on whether a pre-emptive approach or primary antiviral prophylaxis is the best solution in this setting of patients. In addition, questions still unresolved are the type of prophylactic drug against HBV and adequate prophylaxis duration. Methods In this case-cohort study, we compared a prospective series of 31 HBsAg−/HBcAb+ patients with newly diagnosed high-risk DLBCL receiving lamivudine (LAM) prophylaxis 1 week before R-CHOP-21+2R until 18 months after (24-month LAM series) versus 96 HBsAg−/HBcAb+ patients (from January 2005 to December 2011) undergoing a pre-emptive approach (pre-emptive cohort) and versus 60 HBsAg−/HBcAb+ patients, from January 2012 to December 2017, receiving LAM prophylaxis [1 week before immunochemotherapy (ICHT) start until 6 months after] (12-month LAM cohort). Efficacy analysis focused primarily on ICHT disruption and secondarily on OBI reactivation and/or acute hepatitis. Results In the 24-month LAM series and in the 12-month LAM cohort, there were no episodes of ICHT disruption versus 7% in the pre-emptive cohort (P = 0.05). OBI reactivation did not occur in any of the 31 patients in the 24-month LAM series versus 7 out of 60 patients (10%) in the 12-month LAM cohort or 12 out of 96 (12%) patients in the pre-emptive cohort (P = 0.04, by χ2 test). No patients in the 24-month LAM series developed acute hepatitis compared with three in the 12-month LAM cohort and six in the pre-emptive cohort. Discussion This is the first study collecting data regarding a consistent and homogeneous large sample of 187 HBsAg−/HBcAb+ patients undergoing standard R-CHOP-21 for aggressive lymphoma. In our study, 24-month-long prophylaxis with LAM appears to be the most effective approach with a null risk of OBI reactivation, hepatitis flare-up, and ICHT disruption.